2019
DOI: 10.1080/22221751.2019.1701391
|View full text |Cite
|
Sign up to set email alerts
|

Genetic manipulation of porcine deltacoronavirus reveals insights into NS6 and NS7 functions: a novel strategy for vaccine design

Abstract: Porcine deltacoronavirus (PDCoV) is an emerging swine coronavirus that causes severe diarrhea, resulting in high mortality in neonatal piglets. Despite widespread outbreaks in many countries, no effective PDCoV vaccines are currently available. Here, we generated, for the first time, a full-length infectious cDNA clone of PDCoV. We further manipulated the infectious clone by replacing the NS6 gene with a green fluorescent protein (GFP) to generate rPDCoV-ΔNS6-GFP; likewise, rPDCoV-ΔNS7 was constructed by remov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 41 publications
1
36
0
Order By: Relevance
“…The low N gene level of icDelNS6/nG reflects the growth kinetics and western blotting results ( Fig. 6 C and E) and is likely due to impaired viral replication caused by the insertion of a foreign gene ( Zhang et al, 2020 ). Even though the impaired viral replication may delay the induction of IFN-β and ISGs, similar IFN-β mRNA levels were observed (16 hpi of icPDCoV vs 24 hpi of icDelNS6/nG) when both viruses had comparable levels of N gene at these time points ( Fig.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…The low N gene level of icDelNS6/nG reflects the growth kinetics and western blotting results ( Fig. 6 C and E) and is likely due to impaired viral replication caused by the insertion of a foreign gene ( Zhang et al, 2020 ). Even though the impaired viral replication may delay the induction of IFN-β and ISGs, similar IFN-β mRNA levels were observed (16 hpi of icPDCoV vs 24 hpi of icDelNS6/nG) when both viruses had comparable levels of N gene at these time points ( Fig.…”
Section: Resultsmentioning
confidence: 70%
“…The functions of NS6, NS7, and NS7a remain unclear. One study reported that recombinant PDCoV with the ATG of NS7 removed had no diminishing effect on strain CHN-HG-2017 virulence and that NS6 could be replaced by a green fluorescent protein (GFP) with a reduction in clinical signs, yet no sequence verification after inoculation into swine was completed to fully understand the underlying genetic basis for the phenotype ( Zhang et al, 2020 ). Another study reported that NS6 could antagonize IFN-β production when it was ectopically expressed ( Fang et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has shown that PDCoV NS6 was expressed and distributed in the cytoplasm during early virus infection and antagonizes IFN-β production in vitro ( Fang et al, 2018 ). In addition, Zhang et al generated a NS6-null recombinant PDCoV mutant by reverse genetics and showed that NS6 play a key role in promoting viral replication and pathogenesis ( Zhang et al, 2020 ). However, whether the NS6 is expressed in target tissues of infected pigs was not assessed yet.…”
Section: Discussionmentioning
confidence: 99%
“…NS6 was found to antagonize IFN-β production by interacting with RIG-I and MDA5 to impede their association with double-stranded RNA ( Fang et al, 2018 ). Recently, a recombinant virus (rPDCoV-ΔNS6-GFP), in which the NS6 gene was replaced by the green fluorescent protein (GFP) gene, has been constructed by reverse genetics ( Zhang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The diverse dimerization forms of nsp9 protein could enhance their nucleic acid binding affinity (104). ns6 protein is an important virulence factor of PDCoV (105). It is known that N, nsp5, nsp15, ns6 contribute to inhibit interferon-β production (106)(107)(108)(109).…”
Section: Apoptosis Associated With Porcine Deltacoronavirus (Pdcov) Vmentioning
confidence: 99%